Pengaruh Parameter Number Of Excitation (NEX) Terhadap SNR - Dwi Rochmayanti; Thomas Sri Widodo; Indah Soesanti (Faculty of Engineering, Universitas Gadjah Mada, 2010)
This research aims to observe the influence of Number of Excitation (NEX) to bothparameters the Signal to Noise Ratio (SNR) and the scanning time when performing the MRneck . Some MR scan parameters (TR, TE, FOV, slice thickness, matrix, flip angle andbandwidth) are strictly under controlled. All SNR data, due to the 6 NEX variations (NEX 1 toNEX 6), are required by comparing the ROI’s intensity between the noise background and theareas of corpus and spinal cord on the images. The scan times are also recorded for each of theNEX variations being observed. In conclusion, increasing NEX values will simultaneously risethe SNR and the scanning time.Keywords : NEX, SNR, Image MRI, Scan time